Serum cytokine change profile associated with HBsAg loss during combination therapy with PEG-IFN-α in NAs-suppressed chronic hepatitis B patients - Wang, Wen-Xin; Jia, Rui; Jin, Xue-Yuan; Li, Xiaoyan; Zhou, Shuang-Nan; Zhang, Xiao-Ning; Zhou, Chun-Bao; Wang, Fu-Sheng; Fu, Junliang (Frontiers in Immunology, 2023)
Objective The aim of this study was to explore the profile of cytokine changes during the combination therapy with pegylated interferon alpha (PEG-IFN-α) and its relationship with HBsAg loss in nucleos(t)ide analogs (NAs)-suppressed chronic hepatitis B patients. Methods Seventy-six patients with chronic hepatitis B with HBsAg less than 1,500 IU/ml and HBV DNA negative after receiving ≥ 1-year NAs therapy were enrolled. Eighteen patients continued to take NAs monotherapy (the NAs group), and 58 patients received combination therapy with NAs and PEG-IFN-α (the Add-on group). The levels of IFNG, IL1B, IL1RN, IL2, IL4, IL6, IL10, IL12A, IL17A, CCL2, CCL3, CCL5, CXCL8, CXCL10, TNF, and CSF2 in peripheral blood during treatment were detected. Results At week 48, 0.00% (0/18) in the NAs group and 25.86% (15/58) in the Add-on group achieved HBsAg loss. During 48 weeks of combined treatment, there was a transitory increase in the levels of ALT, IL1RN, IL2, and CCL2. Compared to the NAs group, CXCL8 and CXCL10 in the Add-on group remain higher after rising, yet CCL3 showed a continuously increasing trend. Mild and early increases in IL1B, CCL3, IL17A, IL2, IL4, IL6, and CXCL8 were associated with HBsAg loss or decrease >1 log, while sustained high levels of CCL5 and CXCL10 were associated with poor responses to Add-on therapy at week 48. Conclusions The serum cytokine change profile is closely related to the response to the combination therapy with PEG-IFN-α and NAs, and may help to reveal the mechanism of functional cure and discover new immunological predictors and new therapeutic targets.